If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 3x + -1x + -8 + -6 + 4 = 32 Reorder the terms: -8 + -6 + 4 + 4x + 3x + -1x = 32 Combine like terms: -8 + -6 = -14 -14 + 4 + 4x + 3x + -1x = 32 Combine like terms: -14 + 4 = -10 -10 + 4x + 3x + -1x = 32 Combine like terms: 4x + 3x = 7x -10 + 7x + -1x = 32 Combine like terms: 7x + -1x = 6x -10 + 6x = 32 Solving -10 + 6x = 32 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 6x = 32 + 10 Combine like terms: -10 + 10 = 0 0 + 6x = 32 + 10 6x = 32 + 10 Combine like terms: 32 + 10 = 42 6x = 42 Divide each side by '6'. x = 7 Simplifying x = 7
| -4(5x-3)+7x=2x-4 | | 6(f+5)-8=2f | | 19u-18u=5 | | 4y-30=y+8+2y-3 | | 200(1)-15=y | | .9x-4.9=.5 | | 5*3v-8=-10 | | -0.25(q-1)+0.5=0.75 | | 200m-75m+57900=61500-175m | | 9x+5(x-2)=2(x-3) | | X^2-2px+9=0 | | [(x)(x)]-7x=44 | | 36-9x=19+8x | | 6p-7=-5p+12 | | 200(1)+15=y | | 4x-2x+15-10-6=19 | | 5y-3=2y-15 | | 200(0)+15=y | | 6-9x=6x-10x+1 | | C=3(a+2b) | | -14=8+h | | 3x+2x-18+13=35 | | 9(3m+4)-7m=-4 | | 200(0)-15=y | | 15q-3[4q-6]=3q+9-9q | | 5x+4=26+46 | | 0.3(3x+0.5)= | | -2(5x+2)=-3x+7 | | 12=6ax-4xb | | -25-(-15)= | | 3+y4=-y8 | | 10(12)=5(18) |